Typology of narrative, identity and ideology of Kurdish society From the story of a mangy woman by Sherzad Hassan based on Jap Lintvelt's theory - Ahmed, Asst.L.Korak Ali (Sulaimani Journal for Humanities, 2025)
Each story uses a certain style of narrative design. In recent decades, the interpretation of stories has focused more on structure and form than on content. In this paper, which is based on the method of "descriptive-analytical" we intend to analyze the story "A Mangan Woman" by Sherzad Hassan using the practical concepts of narrative journalism from the perspective of "Jap Lintvelt". In this regard, we consider four main principles; such as, (cognitive - psychological) principle (time principle) (place principle) (verbal principle). In the cognitive-psychological principles, we discuss the subject of attention and the narrative aspect; In the principle of time, the time of the act of narrative and organization, or the mixture of time; such as the speed and time delay of the narrative, and at the third level (place principle) the location of the narrative is analyzed; In the fourth principle (verbal principle), we explain the narrator's position and grammatical personal pronouns, the temporal value of the verbs, and the degree of speech of the actors in this story. As a result of our research, we conclude that the perspective of this story is central and because both narrators are actors in the story and at the center of the story; He does not change his viewpoint and is only able to convey his thoughts to the reader. They cannot tell the thoughts and beliefs of the other characters in the story. Also, many factors of Kurdish society's identity and ideology and their attitudes towards many issues; Their views on love between men and women, marriage, the appearance of women in Kurdish society, relationships between family members and the role of fathers in the family, etc. are shown in this story and are clearly visible in the narratives of the narrators.
Keywords: Narrative; Perspective; Jaap Lintvelt; Sherzad Hassan; A Mangan Woman